Exercise as a determinant of longevity and healthy aging: a narrative review of current evidence - Czajka, Katarzyna; Bort, Julia; Owczarek-Danowska, Iga; Skobudzińska, Maria; Zadrożna, Katarzyna; Syncerz, Natalia (Quality in Sport, 2026)
BACKGROUND: Population aging is associated with increasing prevalence of chronic diseases, frailty, disability, and cognitive decline. Contemporary medicine increasingly focuses not only on lifespan extension but also on preservation of physical and cognitive function in older adults. Regular physical activity is considered one of the most effective non-pharmacological interventions supporting healthy aging. AIM: This review aims to summarize current evidence on the impact of regular physical activity, particularly combined aerobic and resistance exercise, on longevity, healthspan, frailty reduction, and cognitive health in older adults. MATERIALS AND METHODS: A narrative literature review was conducted using PubMed and Cochrane Library databases, including clinical studies, controlled trials, systematic reviews, and meta-analyses published over the last two decades. Animal studies, case reports, editorials, opinion papers, and non-English publications were excluded. RESULTS: Regular physical activity was consistently associated with reduced all-cause mortality, improved cardiorespiratory fitness, reduced frailty, and better cognitive function in older adults. Evidence suggests that adequate activity levels may reduce mortality risk by 19–30%. Aerobic exercise, HIIT, and resistance training improve VO₂max, cardiovascular health, muscle strength, and functional independence, while reducing sarcopenia and fall risk. Physical activity is also linked to enhanced neuroplasticity and a lower risk of dementia, whereas prolonged sedentary behavior increases the risk of cognitive decline. CONCLUSIONS: Regular physical activity, particularly combined aerobic and resistance exercise, remains one of the most evidence-based strategies for promoting longevity and healthy aging. Structured exercise programs may play a central role in preventive and geriatric medicine by improving healthspan, preserving independence, and reducing frailty in aging populations.